2022
DOI: 10.5194/amt-15-5415-2022
|View full text |Cite
|
Sign up to set email alerts
|

An optimal estimation algorithm for the retrieval of fog and low cloud thermodynamic and micro-physical properties

Abstract: Abstract. A new generation of cloud radars, with the ability to make observations close to the surface, presents the possibility of observing fog properties with better insight than was previously possible. The use of these instruments as part of an operational observation network could improve the prediction of fog events, something which is still a problem for even high-resolution numerical weather prediction models. However, the retrieval of liquid water content (LWC) profiles from radar reflectivity alone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For the absolute humidity, the maximum dry bias of the MWR is around 1.4 g m −3 in the lowest troposphere up to 1.7 km and becomes wet above (0.3 g m −3 ). Martinet et al (2022) showed that the LWP accuracy has been validated in clear-sky conditions and has shown errors between 1 and 14 g m −2 . These error range are in the scope of those defined in the literature (Crewell and Löhnert, 2003;Marke et al, 2016).…”
Section: Temperature Liquid Water Content and Wind Profilingmentioning
confidence: 99%
See 3 more Smart Citations
“…For the absolute humidity, the maximum dry bias of the MWR is around 1.4 g m −3 in the lowest troposphere up to 1.7 km and becomes wet above (0.3 g m −3 ). Martinet et al (2022) showed that the LWP accuracy has been validated in clear-sky conditions and has shown errors between 1 and 14 g m −2 . These error range are in the scope of those defined in the literature (Crewell and Löhnert, 2003;Marke et al, 2016).…”
Section: Temperature Liquid Water Content and Wind Profilingmentioning
confidence: 99%
“…every 10 min with a zenith pointing each 1 s. Using neural networks, brightness temperatures measured by the MWR at all elevation angles (the lower elevations angles added to measurements at zenith) are inverted to temperature and humidity variables. More details on this method can be found in Martinet et al (2022). Comparing temperature and humidity profiles retrieved by the MWR with radiosonde data, Martinet et al (2022) found that air temperature has cold biases below 0.5 K in absolute value below 2 km but increases up to 1.5 K above 4 km altitude.…”
Section: Temperature Liquid Water Content and Wind Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation strategy combined vertical profiles derived from remote sensing instruments (microwave radiometer (MWR), Doppler cloud radar and Doppler lidars) and balloon-borne in-situ measurements of fog microphysics and thermodynamics. Bell et al (2022) and Vishwakarma et al (2023) combined cloud radar reflectivity with temperature and humidity profiles and LWP retrieved from MWR, to better estimate the vertical profile of LWC in the fog layer. They demonstrated that LWC retrieval is highly sensitive to the prescribed droplet concentration, and that agreement with in situ data is highly dependent on cloud-fog heterogeneity.…”
Section: Introductionmentioning
confidence: 99%